A Neuroprotective Function of NSF1 Sustains Autophagy and Lysosomal Trafficking in Drosophila. Issue 2 (17th December 2014) - Babcock, Daniel T; Shen, Wei; Ganetzky, Barry
Abstract: A common feature of many neurodegenerative diseases is the accumulation of toxic proteins that disrupt vital cellular functions. Degradative pathways such as autophagy play an important protective role in breaking down misfolded and long-lived proteins. Neurons are particularly vulnerable to defects in these pathways, but many of the details regarding the link between autophagy and neurodegeneration remain unclear. We previously found that temperature-sensitive paralytic mutants in Drosophila are enriched for those exhibiting age-dependent neurodegeneration. Here we show that one of these mutants, comatose ( comt ), in addition to locomotor defects, displays shortened lifespan and progressive neurodegeneration, including loss of dopaminerigic (DA) neurons. comt encodes N-ethyl-maleimide sensitive fusion protein (NSF1), which has a well-documented role in synaptic transmission. However, the neurodegenerative phenotypes we observe in comt mutants do not appear to depend on defects in synaptic transmission, but rather from their inability to sustain autophagy under stress, due at least in part to a defect in trafficking of lysosomal proteases such as cathepsin-L. Conversely, overexpression of NSF1 rescues α-synuclein-induced toxicity of DA neurons in a model of Parkinson's disease. Our results demonstrate a neuroprotective role for NSF1 that involves mediation of fusion events crucial for degradative pathways such as autophagy, providing greater understanding of cellular dysfunctions common to several neurodegenerative diseases.